Functional Characterization of Olfactory Proteins Involved in Chemoreception of Galeruca daurica - Li, Ling; Zhang, Wen-Bing; Shan, Yan-Min; Zhang, Zhuo-Ran; Pang, Bao-Ping (Frontiers in Physiology, 2021)
Odorant binding proteins (OBPs) and chemosensory proteins (CSPs) play a fundamental role in insect olfaction. Galeruca daurica (Joannis) is a new pest with outbreak status in the Inner Mongolia grasslands, northern China. In this study, six olfactory protein genes (GdauOBP1, GdauOBP6, GdauOBP10, GdauOBP15, GdauCSP4 and GdauCSP5) were cloned by RACE, and expressed by constructing prokaryotic expression system. Their binding affinities were measured for 13 volatiles from the host plant (Allium mongolicum) by the fluorescence competitive binding assays. To further verify the olfactory functions of GdauOBP15 and GdauCSP5, RNA interference (RNAi) and electrophysiological recording were conducted. Ligand-binding assays showed that six recombinant proteins displayed different degrees of binding affinities to the tested volatiles. GdauOBP6, GdauOBP15, GdauCSP4, and GdauCSP5 could bind several tested ligands of host plants. It was suspected that GdauOBP6, GdauOBP15, GdauCSP4, and GdauCSP5 were related to host location in G. daurica. It was found that there were different EAG responses between males and females when the GdauOBP15 and GdauCSP5 genes were silenced by RNAi. The EAG response of G. daurica females to 2-hexenal was significantly decreased in dsRNA-OBP15 injected treatment compared to the control, and the dsRNA-CSP5 treated females significantly reduced EAG response to eight tested host volatiles (1,3-dithiane, 2-hexenal, methyl benzoate, dimethyl trisulfide, myrcene, hexanal, 1,3,5-cycloheptatriene, and p-xylene). However, the EAG response had no significant difference in males. Both GdauOBP15 and GdauCSP5 may have different functions in odor perception between males and females in G. daurica, and may play more important roles in females searching host plants.